An uncommon presentation of abdominal mass in an infant: A case report of fetus in fetu - Muhammad Idrees, MBBS; Mushtaq Ahmed, MBBS, FCPS; Waleed Tariq, BSc, MBBS; Muhammad Junaid Tahir, BSc, MBBS; Anis ur Rehman, MBBS, FRCR (Radiology Case Reports)
Owing to the rare existence of fetus in fetu (FIF) with an incidence of one per 500,000 live births worldwide, embryologically it is characterized as diamniotic, monochorionic, monozygotic twins partially developing within the twin body. We present a case of a 10-month-old female suffering from progressively increasing abdominal distention and an immobile abdominal mass which was highlighted on contrast-enhanced computed tomography (CECT) consisting of soft tissue, gaseous, and fluid components. It was deciphered after surgical intervention as a stunted fetus characterized by the presence of structures such as the auricle, eye impressions, limb, vertebral column, brain, and gastrointestinal tissue. Such findings suggest the case of a fetus in fetu. Fetus in fetu must be considered as a differential diagnosis among infants and young children presenting with abdominal distention. Such a presentation must never be overlooked and probed clinically and radiologically, followed by surgical intervention to relieve the pressure effect over the viscera and abdomen.